Posteromedial Ligament Repair of the Knee with Suture Tape Augmentation: A Biomechanical Comparison with Posteromedial Ligament Reconstruction. Issue 5 (28th May 2020) - Mehl, Julian; Kia, Cameron; Obopilwe, Elifho; Cote, Mark; Imhoff, Florian; Otto, Alexander; Arciero, Robert A.; Beitzel, Knut; Imhoff, Andreas B.
Aims and Objectives: ACL ruptures combined with injuries of the superficial medial collateral ligament and posterior oblique ligament (= posteromedial ligament complex; PMC) are common. In acute cases with high-grade valgus and rotatory instability, primary repair of the PMC with suture tape augmentation may be a reasonable alternative to standard reconstruction techniques, in order to stabilize the knee and to protect the reconstructed ACL. The aim of the present study was to biomechanically examine the rotational and valgus stability, as well as the influence on ACL strain, following PMC repair with suture tape augmentation in comparison with posteromedial ligament reconstruction using tendon grafts. Materials and Methods: Ten cadaveric knee specimens were tested with the tibia fixed and the femur mobile on an X-Y-table. Each specimen was tested in four different conditions according to the state of the PMC: 1) native, 2) femoral avulsion, 3) repaired with suture tape augmentation, 4) reconstructed with tendon allografts. Valgus instability was tested with 40 N force applied in the lateral direction of the femur and rotational motion was tested with 5 N torque applied to the tibia. An optical 3D motion tracking system captured the valgus angle and the internal and external rotation. Additionally, the strain on the ACL during valgus stress was measured with a DVRT. Each condition was tested in 0°, 15°, 30°, 45° and 60° of knee flexion. Results: Femoral avulsion of the PMC led to a significant increase in valgus instability in all flexion angles and to a significant increase on ACL strain at 30° (Native 1.37 ± 2.33 vs. deficient 7.49 ± 7.00; p<0.001) and 45° (0.88 ± 1.66 vs. 2.82 ± 2.59; p<0.001) knee flexion. Additionally, a significant increase of internal rotation in 0° (p=0.018) and 30° (p=0.005) knee flexion and a significant increase of external rotation in 15° (p<0.001), 30° (p=0.016), 45° (p=0.006) and 60° (p=0.012) knee flexion was seen after dissection of the PMC. PMC repair with suture tape augmentation demonstrated similar valgus and rotational stability compared to intact specimens, with the exception of increased internal rotation at 30° (16.2 ± 6.3° vs. 19.3 ± 6.9°; p=0.005). PMC reconstruction with tendon grafts led to a significantly increased valgus opening at a 45° degree of knee flexion (7.5 ± 2.9° vs. 8.9 ± 2.1°; p=0.048) and significantly increased internal rotation at 30° (16.2 ± 6.3° vs. 20.1 ± 7.3°; p<0.001) compared to the native state. Direct comparison between both surgical techniques showed no significant differences. Conclusion: At time zero, ligament repair of the posteromedial knee with suture tape augmentation restored close to native valgus and rotatory stability, as well as native ACL strain for cases of complete PMC avulsion. Posteromedial ligament repair with suture tape augmentation may be a reasonable alternative to tendon reconstruction techniques in acute cases of combined posteromedial and ACL injuries with high-grade valgus and rotatory instability.